THE INFLUENCE OF CREATIVE PROBLEM SOLVING LEARNING MODEL SUPPORTED WITH REAL OBJECT MEDIA ON THE ABILITY TO SOLVE PROBLEMS RELATED TO SIMPLE SOLVINGS IN THIRD GRADE STUDENTS AT MIN 1 ACEH TENGAH - Hilliyani Hilliyani; Nanang Khuzaini (Renjana Pendidikan Dasar, 2023)
This research is motivated by the results of observations, that mathematics learning activities in elementary schools still tend to be dominated by teachers with lecturing activities. This is what causes students to become passive and do not understand the material so that it affects low student learning outcomes. This study used a quantitative approach with a pretest-posttest control group design and research subjects of class III MIN 1 Aceh Tengah. The research was conducted using two classes, namely experimental and control. The instruments used are learning tools and test sheets in the form of description questions. To analyze the data, researchers used SPSS 16.0 for windows software. The results showed that (1) the ability of students to solve simple fraction problems using creative problem solving learning models supported by real object media increased with an average value of 84.00 or > 75% achieving KKM. (2) The ability to solve simple fraction problems using conventional learning models without the support of real object media tends to be low with an average score of 69.18 or <75% which achieves KKM. (3) There is a significant effect on the ability to solve simple fraction problems using the Creative Problem Solving learning model supported by real object media with Asymp. Sig. (2- tailed) 0.000 < 0.05, tcount > ttable, 7.744 > 2.032.